PENANGGULANGAN STRES PADA REMAJA PASCA LULUS SEKOLAH - Frista Fitriany Ramadhanita; Alan Putra Muda (Jurnal Bimbingan Penyuluhan Islam, 2023)
This study aims to explore effective stress management in post-graduate adolescents. Adolescents in this transitional stage often experience high levels of stress due to academic pressures, uncertainty about the future, and significant social changes. The aim of this research is to identify stress coping strategies that can help adolescents cope with stress and improve their well-being. This research method is a literature study, which involves collecting and analyzing previous works related to stress management in post-graduate adolescents. Research highlights strategies that have been proven effective, such as building social support, planning a clear future, maintaining physical health, setting realistic goals, managing time well, maintaining balance in life, developing stress management skills, avoiding substance use, and seek professional help. The results of this study indicate that implementing these stress management strategies can help post-graduate adolescents reduce stress levels and improve their overall well-being. Appropriate social support and career guidance have also proven important in helping adolescents cope with the pressures they experience. These findings indicate the need for a holistic approach in dealing with stress in post-graduate adolescents, involving various factors such as social support, planning for the future, and paying attention to physical and mental health. The practical implication of this research is the importance of paying attention to the well-being of adolescents in this transitional stage and providing them with effective tools for managing their stress.